Rod-on-flake α-FeOOH/BiOI nanocomposite: Facile synthesis, characterization and enhanced photocatalytic performance - Malathi, A.; Arunachalam, Prabhakarn; Madhavan, J.; Al-Mayouf, Abdullah M.; Ghanem, Mohamed A. (Colloids and surfaces. A, Physicochemical and engineering aspects, 2018)
[Display omitted] •α-FeOOH/BiOI nanocomposites were synthesized successfully by wet impregnation method.•α-FeOOH/BiOI nanocomposite exhibited greatly enhanced photocatalytic activity.•The mechanism of the enhanced photocatalytic activity was discussed in detail. Herein, we have prepared different weight percentages of (10%, 20% and 30%) of α-FeOOH on BiOI visible light active α-FeOOH/BiOI nanocomposite via facile wet impregnation method. The rod-like morphology of α-FeOOH and flake-like morphology of BiOI photocatalyst were fabricated via hydrothermal process. The synthesized photocatalyst were explored by different characterization methods such as FT-IR, XRD, FE-SEM, EDAX, HR-TEM and UV–vis DRS. The photocatalytic behavior was assessed by the photodegradation of Rhodamine B (RhB) under visible-light illumination. The optimum 10% α-FeOOH/BiOI nanocomposite showed a superior photocatalytic activity than other photocatalysts. About 91% degradation of RhB was witnessed after 90min under illumination. Further, the photoluminescence (PL) and photoelectrochemical measurements revealed that the 10% α-FeOOH/BiOI nanocomposite showing enhanced charge carrier separation than other photocatalysts. The superior photocatalytic activity and photostability revealed that the α-FeOOH/BiOI nanocomposite could be a promising material in wastewater treatment and other environmental remediation applications.